MicroRNA-200a/200b Modulate High Glucose-Induced Endothelial Inflammation by Targeting O-linked N-Acetylglucosamine Transferase Expression - Lo, Wan-Yu; Yang, Wen-Kai; Peng, Ching-Tien; Pai, Wan-Yu; Wang, Huang-Joe (Frontiers in Physiology, 2018)
Background and Aims: Increased O-linked N-acetylglucosamine (O-GlcNAc) modification of proteins by O-GlcNAc transferase (OGT) is associated with diabetic complications. Furthermore, oxidative stress promotes endothelial inflammation during diabetes. A previous study reported that microRNA-200 (miR-200) family members are sensitive to oxidative stress. In this study, we examined whether miR-200a and miR-200b regulate high-glucose (HG)-induced OGT expression in human aortic endothelial cells (HAECs) and whether miRNA-200a/200b downregulate OGT expression to control HG-induced endothelial inflammation. Methods: HAECs were stimulated with high glucose (25 mM) for 12 and 24 h. Real-time polymerase chain reaction (PCR), western blotting, THP-1 adhesion assay, bioinformatics predication, transfection of miR-200a/200b mimic or inhibitor, luciferase reporter assay, and transfection of siRNA OGT were performed. The aortic endothelium of db/db diabetic mice was evaluated by immunohistochemistry staining. Results: HG upregulated OGT mRNA and protein expression and protein O-GlcNAcylation levels (RL2 antibody) in HAECs, and showed increased intercellular adhesion molecule 1 (ICAM-1), vascular cell adhesion molecule 1 (VCAM-1), and E-selectin gene expression; ICAM-1 expression; and THP-1 adhesion. Bioinformatics analysis revealed homologous sequences between members of the miR-200 family and the 3′-untranslated region (3′-UTR) of OGT mRNA, and real-time PCR analysis confirmed that members of miR-200 family were significantly decreased in HG-stimulated HAECs. This suggests the presence of an impaired feedback restraint on HG-induced endothelial protein O-GlcNAcylation levels because of OGT upregulation. A luciferase reporter assay demonstrated that miR-200a/200b mimics bind to the 3′-UTR of OGT mRNA. Transfection with miR-200a/200b mimics significantly inhibited HG-induced OGT mRNA expression, OGT protein expression; protein O-GlcNAcylation levels; ICAM-1, VCAM-1, and E-selectin gene expression; ICAM-1 expression; and THP-1 adhesion. Additionally, siRNA-mediated OGT depletion reduced HG-induced protein O-GlcNAcylation; ICAM-1, VCAM-1, and E-selectin gene expression; ICAM-1 expression; and THP-1 adhesion, confirming that HG-induced endothelial inflammation is partially mediated via OGT-induced protein O-GlcNAcylation. These results were validated in vivo: tail-vein injection of miR-200a/200b mimics downregulated endothelial OGT and ICAM-1 expression in db/db mice. Conclusion: miR-200a/200b are involved in modulating HG-induced endothelial inflammation by regulating OGT-mediated protein O-GlcNAcylation, suggesting the therapeutic role of miR-200a/200b on vascular complications in diabetes.